A Delphi study and International Consensus Recommendations: The use of bolus in the setting of postmastectomy radiation therapy for early breast cancer. (November 2021) - Kaidar-Person, Orit; Dahn, Hannah M.; Nichol, Alan M.; Boersma, Liesbeth J.; de Ruysscher, Dirk; Meattini, Icro; Pignol, Jean-Philippe; Aristei, Cynthia; Belkacemi, Yazid; Benjamin, Dori; Bese, Nuran; Coles, Charlotte E.; et al.
Highlights: In the setting of Postmastectomy radiation therapy (PMRT) bolus was not proven to reduces the risk of local recurrences. The use of bolus for PMRT increases the risk of early and late toxicity. The use of bolus should be limited to highly selected cases, where the skin is deemed to be within the clinical target volume. Abstract: Bolus serves as a tissue equivalent material that shifts the 95–100% isodose line towards the skin and subcutaneous tissue. The need for bolus for all breast cancer patients planned for postmastectomy radiation therapy (PMRT) has been questioned. The work was initiated by the faculty of the European SocieTy for Radiotherapy & Oncology (ESTRO) breast cancer courses and represents a multidisciplinary international breast cancer expert collaboration to optimize PMRT. Due to the lack of randomised trials evaluating the benefits of bolus, we designed a stepwise project to evaluate the existing evidence about the use of bolus in the setting of PMRT to achieve an international consensus for the indications of bolus in PMRT, based on the Delphi method.